Ameliorating effects of exercise on disrupted epididymal sperm parameters in high fat diet-induced obese rats - ERCAN, FERİHA (MARMARA UNIV, FAC MEDICINE, 2019)
Objective: Obesity causes male infertility problems and affects the sperm quality. Recent studies have shown that exercise has positive effects on male fertility. The present study aimed to show the effects of swimming exercise on the epididymal sperm number, motility and morphology in hight fat diet (HFD)-induced obese rats. Materials and Methods: Four experimental groups (n=8 in each group) were formed. Standard (STD) and STD+Exercise (STD+EXC) groups were fed with standard rat diet (6% of calories as fat); HFD and HFD+Exercise (HFD+EXC) groups were fed with high fat diet (45% of calories as fat) for 18 weeks. The rats in STD+EXC and HFD+EXC groups were trained by swimming sessions (1 h per day for 5 days a week) during the last 6 weeks of the experiment. The left caudal epididymis was prepared to evaluate the number, motility and morphology of the spermatozoa. The right epididymal samples were processed for histological evaluation. Results: Normospermic parameters were seen in STD and STD+EXC groups. Sperm number and motility decreased and spermatozoa with abnormal morphology increased significantly in HFD group when compared with STD group. A large number of spermatozoa in the epididymal duct lumen and regular morphology of the fibromuscular connective tissue were observed in STD and STD+EXC groups. Most of the epididymal ducts consisted of decreased amount of spermatozoal accumulation in the HFD group. Degenerated pseudostratified columnar epithelium with vacuole formation were additional findings in this group. On the other hand, swimming exercise had an enhancement effect on sperm parameters with prominent spermatozoal accumulation in the ducts of epididymis in HFD induced obese rats. Conclusion: This study shows that HFD-induced obesity decreased the number and motility of spermatozoa, increased abnormal spermatozoa and caused disrupted epididymal morphology. We hypothesize that exercise enhanced HFD-induced spermatogenic and epididymal damages by the regulation of scrotal heat and possible inhibition of oxidative damage in the epididymis.
Keywords: High fat diet; Exercise; Sperm parameters; BODY-MASS INDEX; METABOLIC SYNDROME; SEMEN PARAMETERS; MEN; TESTOSTERONE; IMPACT; ASSOCIATION; HEALTH